Effects of soil bund and landscape positions on selected soil physico-chemical properties at Anole watershed, Rift Valley Basin, Ethiopia - Markos Mathewos; Mesfin Lukas (Environmental Research Communications)
Land degradation in the form of soil erosion and fertility reduction is a major environmental problem in Ethiopia. Various efforts to control soil erosion through the introduction of soil and water conservation measures have been underway for nearly five decades in Ethiopia. The purpose of this research was to assess the effects of soil bunds on selected soil physical and chemical properties in the Anole watershed of Rift Valley of Ethiopia. A reconnaissance survey was conducted to identify a representative soil sampling site. 18 composite soil samples were collected from soil bund and no conservation practice (control) with three replications at three slope positions from 0 to 30 cm depth, whereas, 18 undisturbed soil samples were collected for bulk density analysis from both land uses. The analysis was carried out using analysis of variance (ANOVA). Clay, sand, BD, CEC, TN, and OM showed significant variation (P < 0.05) between the soil bund and control plots. Whereas, for slope positions, sand, clay, BD, CEC, TN, and available phosphorus in the Anole watershed were found to be statistically significant (P < 0.05). In steep, middle, and lower slopes, contents of OC and exchangeable potassium were greater in fields with soil bunds than without. Lower slope fields showed greater clay, OM, and nutrients than steep slopes. Because of the implementation of soil bund in the study watershed, the majority of soil’s physical and chemical characteristics have shown improvement. Proper implementations of soil bunds in the study area have a pronounced positive impact and should be practiced and applied in adjacent watersheds and similar agroecologies in the Rift Valley of Ethiopia.